Power and Aristocracy – Transformation and Composition of the Komnenos “Clan” (1081–1200) – A Statistical Approach - Lachowicz, Paweł (Studia Ceranea, 2020)
The fall of imperial authority and the decline of the Byzantine state at the end of the 12th century has its cause not only in foreign policy but also, to a large extent, in the family policy of the Komnenoi emperors. The “clan” system introduced during Alexios I’ reign and continued by his successors, connected the aristocratic elites with the imperial family by blood ties. In the 12th century, the composition of this group, linked by a complicated marriage network, underwent a significant transformation, which could be one of the most important factors of the later crisis. The purpose of this paper is twofold. First: distinguishing two groups of aristocrats within the Komnenos “clan” i.e. “core” Komnenos family and affine families. Second: determining their approximate numer during the 12th century. Relatively large amount of data about aristocratic elites of that period allows for statistical approach. Written sources and sigillography of the 12th century Byzantium is rich in information about high ranking persons. In addition, the Komnenos era has been thoroughly described in prosopographical works. This allows for counting the number of aristocrats and thus obtaining reliable results. Such an approach is not free from estimation and probability. However, the amount of information is sufficient enough to show the overall trends visible in the composition of the elites associated with the Komnenoi. The result of this study is a table that shows the tendency of the weakening of the Komnenos family in face of a constantly growing group of affine aristocratic families. This sheds a new light on the progressive collapse of the imperial authority after the death of Manuel I Komnenos, the key role of destructive actions of Andronikos I, and the weakness of the Angelos dynasty.